Long-Term Effects of Maternal Deprivation on the Neuronal Soma Area in the Rat Neocortex. (8th May 2014) - Aksić, Milan; Radonjić, Nevena V.; Aleksić, Dubravka; Jevtić, Gordana; Marković, Branka; Petronijević, Nataša; Radonjić, Vidosava; Filipović, Branislav
Abstract : Early separation of rat pups from their mothers ( separatio a matrem ) is considered and accepted as an animal model of perinatal stress. Adult rats, separated early postnatally from their mothers, are developing long-lasting changes in the brain and neuroendocrine system, corresponding to the findings observed in schizophrenia and affective disorders. With the aim to investigate the morphological changes in this animal model we exposed 9-day-old (P9) Wistar rats to a 24 h maternal deprivation (MD). At young adult age rats were sacrificed for morphometric analysis and their brains were compared with the control group bred under the same conditions, but without MD. Rats exposed to MD had a 28% smaller cell soma area in the prefrontal cortex (PFCX), 30% in retrosplenial cortex (RSCX), and 15% in motor cortex (MCX) compared to the controls. No difference was observed in the expression of glial fibrillary acidic protein in the neocortex of MD rats compared to the control group. The results of this study demonstrate that stress in early life has a long-term effect on neuronal soma size in cingulate and retrosplenial cortex and is potentially interesting as these structures play an important role in cognition.